1991
DOI: 10.1021/np50076a015
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Synthesis of Sesquiterpene Lactones, 12. Synthesis of (+)-Colartin, (+)-Arbusculin A and Their C-4 Epimers and Their Biological Activities

Abstract: Colartin [9] and arbusculin A [11] have been synthesized from alpha-santonin [1] in 14.5% (11 steps) and 9.3% (13 steps) overall yields, respectively. Arbusculin A [11] and compounds 20, 21, and 22, which were derived from intermediate 2, showed significant cell growth inhibitory activity against murine lymphocytic leukemia (P-388) in vitro. Plant growth regulating activity of 11 and its synthetic intermediates 4, 5, 8, and 9 was also studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…In a re cent report, the antiinflammatory activity of A. inculta ex tract, without testing any pure compound, was associated with the presence of flavonoids and sesquiterpene lac tones in the extract (4). Several flavonoids (7 10) and some oxygenated sesquiterpenes and sesquiterpene hydrocarbons (11)(12)(13) are known for their antiinflamma tory potential. In the light of the available literature, there is a need to explore different properties of santonin and related terpenoids that may help in understanding the mechanism of the antiinflammatory activity common to several Compositae plants.…”
mentioning
confidence: 99%
“…In a re cent report, the antiinflammatory activity of A. inculta ex tract, without testing any pure compound, was associated with the presence of flavonoids and sesquiterpene lac tones in the extract (4). Several flavonoids (7 10) and some oxygenated sesquiterpenes and sesquiterpene hydrocarbons (11)(12)(13) are known for their antiinflamma tory potential. In the light of the available literature, there is a need to explore different properties of santonin and related terpenoids that may help in understanding the mechanism of the antiinflammatory activity common to several Compositae plants.…”
mentioning
confidence: 99%
“…Therefore, in order to elucidate the structures of these two compounds, the EOs were separated on a silica gel column (Sephadex LH-20), followed by semi-preparative HPLC, which yielded four sesquiterpenes. Peaks 5 and 19 structures were then verified as β-selinene and feropodin after comparison with 1D NMR data reported in the literature, and the absolute configuration of feropodin was further determined using 2D NMR spectra (Ando et al, 1991;Chu et al, 2011). Surprisingly, costunolide (peak 20) and 11,13-dihydrocostunolide (peak 18) were segregated in the EOs.…”
Section: Yield and Compositions Of Eos From The Aerial Part Of A Nakaiimentioning
confidence: 88%
“…A large number of pseudoguaianolides, 4,5-secopseudoguaianolides, guaianolides, and 4,5-secoguaianolides have been shown to exhibit biological activities, including antitumoral [23], root-growth and germination inhibitory activities [24][25][26][27], as well as preventive or curative activities against phytopatogenic fungi [24,26]. Shimoma et al [28] reported the regio-and stereoselective synthesis of common synthetic intermediates via kinetic resolution with Lipase PS, (Fig.…”
Section: Herbicidesmentioning
confidence: 99%